Ethnicity and Economy - Fenton, S. author. aut Link
XI, 222 p.
Keywords: The nature of the connection between economic action and structure and ethnic identities receives here a long overdue and incisive re-examination. The question is addressed theoretically by revisiting the 'race and class' debate and by a wide-ranging review of the contexts in which the conjuncture of ethnicity-economy is worked out. It is also addressed empirically in a series of case studies of ethnically-defined groups and their articulation with the economy. A combination of established authors and new researchers have made an invaluable contribution to the field.